2020
DOI: 10.4314/sajas.v50i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arbuscular mycorrhizal inoculation on the quality and in vitro gas production of einkorn wheat straw

Abstract: The purpose of this study was to determine the effects of arbuscular mycorrhizal (AM) inoculation on the quality of einkorn wheat straw (EWS) and in vitro gas production (GP). It was found that AM inoculation of EW seed before sowing caused significant increases in crude protein (CP), ether extract (EE), neutral detergent fibre (NDF), zinc (Zn), copper (Cu), and iron (Fe) levels of straw, and a (P <0.05) decrease in crude ash (CA), metabolizable energy (ME), and organic matter digestibility (OMD) compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Gas production during in vitro incubation indicates ruminal degradation and microbial activity [ 27 ], and a higher b fraction indicates higher rumen undegradable protein (RUP) content [ 28 ]. Yuan and Wan [ 29 ], and Ayaşan et al [ 30 ] reported negative values for Part a, which is consistent with the findings of the current investigation. However, negative values for Parts a and b are not biologically acceptable.…”
Section: Resultssupporting
confidence: 92%
“…Gas production during in vitro incubation indicates ruminal degradation and microbial activity [ 27 ], and a higher b fraction indicates higher rumen undegradable protein (RUP) content [ 28 ]. Yuan and Wan [ 29 ], and Ayaşan et al [ 30 ] reported negative values for Part a, which is consistent with the findings of the current investigation. However, negative values for Parts a and b are not biologically acceptable.…”
Section: Resultssupporting
confidence: 92%
“…This could be justified by the fact that AMFs can improve inorganic and organic soil N mobilization (Halder et al, 2015). In addition, the increase in the CP content of forage legumes could be attributed to the increase in nutrient uptake of N to extra-radical mycorrhizae hyphae beyond the root hair and nutrient depletion zones (Ayasan et al, 2020). The present results are in line with findings by Ashrafi et al (2014) and Ben-Laouane et al (2021), which indicated that the dual inoculation of AMF and Rhizobia bacteria had a positive effect on the CP content of alfalfa forage legume.…”
Section: Discussionmentioning
confidence: 99%
“…Poor animal nutrition is one of the main factors restricting livestock productivity [8]. Te poor quality, nutrient content, and digestibility of crop residues can be improved and degraded using various methods such as grinding, stream processing, chemical methods (such as alkaline treatments and other chemicals, such as sodium hydroxide, sulfur dioxide, urea, or chlorine), and biological methods (such as fungal treatment, inoculants, enzymes, or alternative additives) have been utilized separately or in combination [12][13][14]. However, improving the nutritional content of crop residues is not very common in Ethiopia due to lack of knowledge, lack of funding, and availability of chemicals for treatment [5,15].…”
Section: Introductionmentioning
confidence: 99%